2011
DOI: 10.1093/carcin/bgq287
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between genetic polymorphisms in the apoptotic pathway and environmental factors on esophageal adenocarcinoma risk

Abstract: How genetic variations in apoptosis pathway interact with environmental factors to contribute to esophageal adenocarcinoma (EA) risk has not been comprehensively investigated. We conducted a case-only analysis in 335 Caucasian EA patients that were genotyped for 242 single nucleotide polymorphisms (SNPs) in 43 apoptotic genes. Gene-environment interactions were assessed using a two-step approach. First, random forest algorithm was used to screen for the potential interacting markers. Next, we used case-only lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…A number of studies have pursued candidate-based gene-environment analyses of EA, and reported interactions between BMI, smoking or GERD symptoms and selected SNPs in genes related to detoxification, angiogenesis, DNA repair, apoptosis, and extracellular matrix degradation. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 This body of work helped to establish the notion that the level of disease risk associated with GERD symptoms, in particular, may vary according to inherited genetic variation. All of these studies, however, were conducted in small samples (<350 cases) and were not replicated in independent populations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have pursued candidate-based gene-environment analyses of EA, and reported interactions between BMI, smoking or GERD symptoms and selected SNPs in genes related to detoxification, angiogenesis, DNA repair, apoptosis, and extracellular matrix degradation. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 This body of work helped to establish the notion that the level of disease risk associated with GERD symptoms, in particular, may vary according to inherited genetic variation. All of these studies, however, were conducted in small samples (<350 cases) and were not replicated in independent populations.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, we considered baseline well-water As as the main exposure because it better measured long-term exposure in our study population. Because > 50% of the 170 SNPs have a variant genotype frequency < 5% and the dominant genetic model is often highly correlated with the additive genetic model ( Lettre et al 2007 ), we conducted all tests for gene–As interactions using dominant genetic model for better statistical power, similar to other gene–environment interaction studies ( Garcia-Closas et al 2013 ; Wu et al 2011 ). SNPs were dichotomized under a dominant genetic model in which genotype with either one or two copies of a minor allele (variant allele) was combined; for SNPs with a negative β AG indicating an antagonistic interaction, we used genotype without the minor allele as the “at-risk” genotype for easy interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…HIF-1 and VEGF ( VEGFA ) -dependent regulation of angiogenesis; 3. lipid biosynthesis; 4. mitochondrial biogenesis and function; 5. cell cycle and growth; and 6. autophagy. All of these effects are modulated/regulated by a large genetic encoding network ( Figure 1 ) ( Table 1 ) [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ,…”
Section: The Biological Effects Of Mtor-imentioning
confidence: 99%